Comparative analysis of maize-livestock innovation systems in Awassa, Bako and Ambo areas of Ethiopia - Mengistu, A. (Haramaya University, 2010)
A study was undertaken with the objectives of (i) assessing farmers’ practices in the use of maize byproducts for livestock feeding and analyze influence of variety on yield and quality of the stover; (ii) analyzing constraints and linkages between maize and livestock subsystems; (iii) assessing factors influencing farmers’ preferences to improved maize varieties, and (iv) describing and understanding the maize-livestock innovation systems at a national level and in selected areas. The study included three levels of analysis, namely the macro, meso and micro levels. The macro level analysis focused on evaluating the national maize – livestock innovation system where key actors, their roles and competencies, their habits and practices, and linkages and interactions were analyzed through review of secondary sources and key informant interviews. The meso level emphasized on the analysis of the innovation systems in Awassa, Bako and Ambo areas, and the assessment of feeding practices and farmers’ rankings of maize varieties through key informant interviews and focus group discussions. Stover samples that were collected at green/eshet and mature/dry stages from on-farm demonstration plots were analyzed for their chemical composition (ash, nitrogen, neutral detergent fiber, acid detergent fiber, acid detergent lignin, in vitro organic matter digestibility and metabolizable energy). Besides, at micro level, household level data were collected from a total sample size of 350 farmers randomly selected from Awassa, Bako Tibe and Ambo districts. Analysis of factors that affect farmers’ choice of varieties was done using the multinomial logit model. Descriptive statistics and ANOVA were also employed as analytical tools. From the studied maize varieties, significant varietal differences were observed in NDF and ADL contents of stovers. However, varietal difference in grain yield was not significant. Results of the current study gave indications about the possibility of manipulating feed related traits in the effort to breed and/or select for maize varieties that combine food and feed traits The linkage between the maize and livestock subsystems towards an integrated maize-livestock production system has been constrained by several problems. These constraints affect resource flows between the two subsystems by constraining both or either. These included socio economic, biophysical and institutional constraints. The ever intensifying population pressure which influences the availability of land for maize production and grazing and large family size of households motivating farmers to cultivate more land dictated by the demand for enough grain are affecting the linkage. Feed shortage coupled with disease problems causes continuous decline of livestock number and productivity constraining the contribution of livestock to the maize subsystem. Unbalanced research and extension focus between the maize and the livestock subsystems, difficulties in the process of technology popularization and inefficient and ineffective input, credit and veterinary services are the important institutional bottlenecks for integrating the maize and livestock subsystems to the level they could. Analysis of the factors that affect farmers’ choice of maize varieties gave results with a possible implication that livestock owning farmers make a preference to a variety with better stover quality in addition to grain yield. There were no functional and meaningful mechanisms of interaction between the actors in the maize livestock innovation system and the different actors have capacity limitations to execute their roles up to the level and quality that the system requires for being effective, efficient and sustainable. The overall picture of the maize-livestock innovation system is tied with the conventional top-down approach which is not participatory and learning based. The system suffers from shortages and high prices of inputs added to lack of timely supply. Lack of proper input demand assessment is also contributing to the scope of the problem. There is a high government control over the input system. Continued capacity building efforts for all of the actors and promotion of trust worthy interactive learning processes for better technological uptake and responsiveness to the demands of end users are necessary. An institutional innovation and building the culture of working together to bring about technological change is required.